Isotopic fractionation of Zn during soil sorption as influenced by soil properties and the Zn–O bond distance: Insights from EXAFS and MC-ICP-MS - Gu, Jiahui; Cui, Peixin; Zeng, Zhen; Sun, Yufang; Sun, Qian; Wang, Yujun (Applied geochemistry, 2022)
Compared to some of the other heavy metals (such as cadmium and lead), zinc (Zn) is a vital trace element for humans and plants but toxic at high concentrations. Stable Zn isotopic techniques have been used to trace the sources of Zn in soils over the past decade. However, sorption processes after Zn enters soil may result in additional isotopic fractionation. This could change the Zn isotopic ratio and result in poor assessment and mismanagement of Zn pollution when using this technique. Different soil properties may have an influence on the Zn sorption process in soils. In this study, we explored the Zn isotopic fractionation in 29 soil samples with different properties (including Zn content, pH, texture, particle size, cation exchange capacity, etc.) using multi-collector inductively coupled plasma mass spectrometry (MC-ICP-MS). Results of path analysis showed that the differences in the Zn isotopic fractionation of different soils mainly arose from the direct effects of Alox, Mnox, and clay, as well as the indirect effects of pH and soil organic matter. Extended X-ray absorption fine structure (EXAFS) analysis showed a positive correlation between Zn isotopic fractionation and the Zn–O bond distance, which conformed to the theory that fractionation factor varies according to bond strength. The results of this study show that different soil properties have varying degrees of impact on Zn isotopic fractionation. And the difference in fractionation can be largely explained by binding conditions of Zn in soils. •Zn isotopic fractionation in 29 soils with different properties is explored using MC-ICP-MS.•The Alox, Mnox, and clay were the most direct influences upon Δ66Zn, while SOM and pH showed more indirect influences.•The difference in Zn isotopic fractionation can be largely explained by binding conditions of Zn in soils.